Phenomenological study of meanings and experiences in managing school funds among public school head teachers - Mwinjuma, Juma Saidi; Abdul Kadir, Suhaida; Hamzah, Azimi; Basri, Ramli (Universiti Putra Malaysia Press, 2016)
This study explored the meanings and experiences that head teachers construed in managing school funds in public primary schools in Tanzania. Descriptive phenomenology was employed to directly explore, analyze and describe head teachers insights about the phenomenon. Seven head teachers were purposively selected based on inclusive criteria of education and years of serving in the headship post. In-depth interview, informal observation and documentary review were used to gather the data. Through descriptive phenomenological analysis bureaucratic procedure, insufficiency and inconsistency of funding and deferred disbursement emerged as themes that reflected head teachers meanings and experiences in managing school fund. Drawing from the findings, this research provides a conclusion and recommendation that would help address issues of practices. Thus, understanding head teachers’ insights are essential for effective resources allocations to schools.